Right external iliac artery thrombus following the use of resuscitative endovascular balloon occlusion of the aorta for placenta accreta. Issue 11 (13th November 2018) - Greer, Jordan W; Flanagan, Colleen; Bhavaraju, Avi; Davis, Ben; Kimbrough, Mary K; Privratsky, Anna; Robertson, Ronald; Taylor, John R; Sexton, Kevin W; Beck, William C
Abstract: A 33-year-old female, 32 weeks and 1 day gestation, with known placenta accreta who presented to the emergency department with 2 h of severe abdominal pain, nausea and vomiting. She became hypotensive and underwent emergency cesarean section. Emergency general surgery was consulted for placement of a resuscitative endovascular balloon for aortic occlusion (REBOA). After successful delivery, the balloon was inflated in zone 3 and systolic blood pressure rose from 70 to 170 mmHg. The patient underwent hysterectomy for ongoing hemorrhage. The patient was taken to the surgical intensive care unit. The patient was noted to have pulses following removal of the sheath. Arterial brachial indices and arterial duplex was performed 48 h after sheath removal. The patient was found to have complete occlusion of the right external iliac artery. Vascular surgery was consulted and cut-down performed with thrombus removal via fogarty catheter. The patient was discharged 2 days later without further complication.